Energy-efficient cable-actuation strategies of the V-Expander tensegrity structure subjected to five shape changes. (January 2023) - Chen, Muhao; Fraddosio, Aguinaldo; Micheletti, Andrea; Pavone, Gaetano; Piccioni, Mario Daniele; Skelton, Robert E.
Abstract: This paper presents the energy-efficient cable-actuation strategy studies of the V-Expander tensegrity subject to different shape changes based on the nonlinear tensegrity dynamics and statics. First, we introduce the topology of a two-stage V-Expander tower assembled by two elementary cells and give the equations ruling the nonlinear statics and dynamics for tensegrity structures. Then, the cable-actuation process is realized by choosing suitable sets of cables as active and passive elements among the whole set of cables. The length of the active cables decreases during actuation, while passive cables adjust their length accordingly following the motion of the structure. Five shape-change types are considered: stretching, shrinking, flexure, shear, and torsion. We analyze the nonlinear static and dynamic behaviors during the morphing process with different actuation speeds. The actuation efficiency of each particular choice of active and passive cables is also discussed. The developed approaches can also be used to design and analyze various cable-driven tensegrity structures. Highlights: The energy-efficient cable-actuation strategies of the V-Expander tensegrity subjected to five shape changes are analyzed. The nonlinear dynamics, statics, and form-finding algorithm of tensegrity structures are given. The nonlinear static and dynamic behaviors during the morphing process with different actuation speeds are studied.